The Scope of Discretionary Authority of the Administrative Body While Proceeding Tax Dispute - Kordzadze, Marine (European Scientific Journal, ESJ, 2017)
Tax dispute is one of the types of administrative proceedings which has its peculiarities. Tax dispute takes place in the Ministry of Finance of Georgia and in the Court. Proceeding of Legal regulation of tax dispute and determining the scope of the discretionary powers of the administrative body is carried out according to the tax code of legal procedures, as well as the General Administrative Code of Georgia, the Administrative Code, the Administrative Procedure Code, the Civil and Civil Procedure Code, Criminal Code, the Law on “Entrepreneurs’’ and other acts. While resolving tax disputes, it is important to define the scope of the discretionary powers of the administrative body.